First third-generation CAR T cell application targeting CD19 for the treatment of systemic IgM AL amyloidosis with underlying marginal zone lymphoma - Korell, Felix; Schönland, Stefan; Schmitt, Anita; Jansen, Madelaine; Farid, Kiavasch; Müller-Tidow, Carsten; Dreger, Peter; Schmitt, Michael; Hegenbart, Ute (Biomarker Research, 2023)
Light chain amyloidosis (AL) is a rare disease caused by the generalized deposition of misfolded free light chains. Patients with immunoglobulin M gammopathy (IgM) and indolent B-cell lymphoma such as marginal zone lymphoma (MZL) may in some instances develop AL amyloidosis. So far, CAR T cells for AL amyloidosis have only been reported utilizing the B cell maturation antigen as target, while CD19 has so far not been used in AL amyloidosis. We report the case of a 71-year-old male, diagnosed with systemic AL kappa amyloidosis and MZL, receiving third-generation CAR T cell therapy targeting CD19. Prior treatment included bendamustine/rituximab and cyclophosphamide/ dexamethasone with subsequent autologous stem cell transplantation. CAR T application was well tolerated despite heart and kidney amyloid manifestations, and only early low-grade procedure-specific toxicities were observed. A continuous decrease in IgM, kappa light chains and kappa-to-lambda light chain difference was observed in the patient from day + 30 on, resulting in a deep hematological response six months after treatment. In summary, we present a novel case of CAR T cell treatment with third generation CD19 directed infusion for AL amyloidosis with an underlying secretory active B cell lymphoma, showing that this is an effective treatment modality and can be applied to patients with subsequent AL amyloidosis.
Veröffentlicht: 14. Oktober 2023
Gesehen am 14.12.2023